College Athletics and Disseminating Sports Betting Data - Ryan Rodenberg (Journal of Applied Sports Management, 2021)
The focus of this article is the interplay between college athletics and sports betting data dissemination, a near-future friction poised for litigation given concurrent issues involving name-image-likeness (NIL) rights and concentration of college sports via mega-conferences.
Keywords: Gambling; NCAA; NIL; Policy; Sponsorships; Student-Athletes